MIGRATION CODE PADA BACKEND CRIMEZONE DARI PHP KE SCALA - Agus Suhendra; Adam Mukharil Bachtiar (Faculty of Computer Science Universitas Indonesia, 2016)
Crimezone is the application of citizen journalism developed to report crimes in Bandung which is available on windows phone platform. In its use, this app still has some problems in the backend system. One that often occurs is failure in sending image stream data with a large size, the provided web service is slow in delivering the requested data, and the backend system is highly vulnerable of web attacks. The purpose of this research is to improve the performance of Crimezone’s backend system. This is achieved by migrating from the current programming language to the new one. The selection of the Scala programming language will improve the performance of the backend system, facilitate use of asynchronous programming, concurrency, and parallelism and improve the security on the system.